Optimization and kinetics modeling of phenolics extraction from coffee silverskin in deep eutectic solvent using ultrasound-assisted extraction - Supawat Taweekayujan; Supitcha Somngam; Tanawan Pinnarat (Heliyon, 2023)
of 0.991-0.999.
Keywords: Ionic liquids properties and applications; Coffee research and impacts; Food Chemistry and Fat Analysis